THE ASSOCIATION OF SURGICAL SAFETY AND PATIENT SAFETY INCIDENT - Romli, Leo Yosdimyati (Universitas Respati Yogyakarta, 2021)
Failure to perform surgical safety could have been caused several unwanted cases and result in disability and even death. This studied aims to analyze the association of surgical safety and patient safety incident. The studied design used was cross-sectional with a population of all surgery patients who was taken by purposive sampling technique. The researched variables was the implementation of surgical safety and patient safety incident. The researched instrument used a checklist with data analysis using the chi-square. the implementation of surgical safety shows mostly good results and there was no patient safety incident (87%), while the implementation of surgical safety shows sufficient results and there was no patient safety incident (7,4%) and patient safety incidents occur (1,9%). The implementation of surgical safety was poorly implemented and there was no patient safety incident (3,7%). The results of statistical analysis using chi-square obtained p-value (0,000) <Î± (0,05): the results showed a significant association regarding the implementation of surgical safety with the patient safety incident. The implementation of surgical safety shows that there was a significant association with incidents of patient safety. Surgical safety was carried out very well so that the findings of a patient safety incident was minimal. Keywords: Surgical Safety; Patient Safety Incident; Surgical; Patient Safety; Incident